Expert-guided approaches to complementary interventions for common side effects of cancer therapies: a practice-based perspective from integrative oncology centers in Baden-Württemberg, Germany - Winkler, Marcela; Breitkreuz, Thomas; Brust, Jürgen; Frenzel, Stefanie; Gottfried, Julia; Heyl, Wolfgang; Hiller, Stefan; Hofheinz, Ralf-Dieter; Jocher, Meike; Kaschdailewitsch, Elke; Lampe, Hans; Livas, Maria; et al. (Frontiers in oncology, 2025)
IntroductionCancer patients commonly suffer from substantial side effects of oncological therapies. Therefore, the Oncology Working Group of the Competence Network for Integrative Medicine in Baden-Württemberg, Germany (KIM-BW) developed practice-oriented recommendations for the integrative treatment of chemotherapy-induced mucositis (CIM), nausea and vomiting (CINV), and cancer-related fatigue (CRF).MethodsTwo expert groups of physicians and nurses developed therapeutic recommendations using an interdisciplinary expert consensus process oriented on a Delphi-methodology with a standardized scoring matrix, considering training, feasibility, time intensity, clinical effectiveness, contraindications, and interactions. The consensus process was complemented by a targeted, non-systematic literature search conducted across the AWMF S3 Guideline on Complementary Medicine in Oncology, the KOKON knowledge database, the Working Group on Integrative Care in Oncology, and PubMed/Medline.ResultsThe expert panel consisted of 21 professionals (14 physicians, 7 nurses), all conventionally trained with additional qualifications in integrative disciplines. We evaluated 83 interventions. Top recommendations were identified for each symptom. For CIM: sage tea mouth rinses, ice cubes, sea buckthorn oil mouth rinses, frozen pineapple cubes, and herbal oral balm. For CRF: movement therapy, yarrow liver compresses, viscum album therapy, sleep hygiene with regular circadian rhythms, and hydrotherapy. For CINV: acupressure, ginger, aromatherapy, bitter botanicals such as gentian root, and homeopathic preparation nux vomica.ConclusionsIntegrative treatment recommendations developed by the KIM Oncology Working Group provide pragmatic, clinically grounded guidance for integrative management of common treatment-related symptoms in oncology. Prospective evaluation of safety, effectiveness, and implementation across settings is warranted.